Freudian slip : psychoanalysis and textual criticism - Timpanaro, Sebastiano (Verso, 1985)
Philology cross-examines Freud in this sustained critique of psychoanalysis and its foundational notion of the slip. Challenging virtually every account of linguistic error in Freud s work as arbitrary and constrained, Sebastiano Timpanaro advances an alternative picture keyed to the dynamics of banalization, disimprovement, and contextual play borrowed from the field of literary criticism. Underscored with a Marxist defense of science against the professed materialism of the psychoanalytic individual drama, Timpanaro s analysis demands a strong reassessment of the Freudian legacy and a renewed debate over its value for the Left."